(E)-2,2 '-[3-(2-Nitrophenyl)prop-2-ene-1,1-diyl]bis(3-hydroxycyclohex-2-en-1-one ) - Cha, Joo Hwan; Kim, Young Hee; Lee, Jae Kyun; Cho, Yong Seo (WILEY-BLACKWELL, 2012)
In the title compound, C(21)H(21)NO(6), each of the cyclohexenone rings adopts a half-chair conformation. Each of the pairs of hydroxy and carbonyl O atoms are oriented to allow for the formation of intramolecular O-H center dot center dot center dot O hydrogen bonds, which are typical of xanthene derivatives.